Optic Nerve Head Parameters and Macular Thickness Analysis by Optical Coherence Tomography in Presenile Patients After Cataract Surgery - Nasima Sultana; Sultana Jesmin Ahmed; Kamal Hasan; Mir Alam Siddique; Sheema Baqtiyar; Md Yamin Hassan (Delhi Journal of Ophthalmology)
Purpose: This study aimed to investigate whether cataract surgery has got any effect on measurements of optic nerve head (ONH) parameters and central macular thickness (CMT) using optical coherence tomography (OCT) in presenile patients. Methods: This study consisted of 18 women and 14 men aged 40-55 years having immature cataract with no previous history of ocular surgery, trauma, eye diseases, and ocular laser procedures. All patients underwent phacoemulsification surgery. Macular thickness and ONH analysis was performed by means of six radial scans centred on the optic disc (fast optic disc acquisition protocol). ONH parameters included rim area, cup area, disc area, cup/disc area ratio, and disc diameter. OCT measurements of operated eyes were done preoperatively, on postoperative day one, day 14, 6 weeks and 24 weeks after surgery using FMT and ONH protocol of OCT. SPSS v 15 (SPSS Inc, Chicago, IL, USA) software was used for the statistical analysis. FMT and ONH parameters were compared with the help of paired sample t – test. Results: The macular thickness after phacoemulsification (PHACO) was highest at 6 weeks with a mean value of221.06±24.36μm. This resolved to near normal value at 24 weeks with mean thickness of 195.73±21.62μm. While analyzing ONH parameters, rim area was 1.50 ± 0.38 mm2 preoperatively which increased significantly in 2nd week (1.67±0.42, p<0.05), 6th week (1.60±0.44, p<0.005) and 24th week (1.57±0.43, p<0.005). Cup area decreased significantly during the 2nd postoperative week (1.17±0.44mm2, p<0.005), 6th week (1.32±0.45mm2, p<0.005) and 24th week (1.31±0.45mm2, p<0.005) in comparison to preoperative value (1.53±0.60mm2, p<0.005). There was significant reduction of cup/disc area ratio after the cataract surgery during the 2nd week (0.40±0.14, p<0.005), 6th week (0.46±0.15, p<0.005) and 24th week (0.47±0.15, p<0.005) in comparison to the cup/disc area ratio prior to surgery (0.49±0.14). There was no statistically significant change in the disc diameter and disc area. Conclusions: Phacoemulsification surgery in presenile cataract causes progressive increase in macular thickness till 6th week which get resolved towards 24 weeks. It causes significant ONH changes with increase in the rim area, reduction in cup area and cup disc area ratio.